Answer:
-1=y
Step-by-step explanation:
Subtract
1
1
11
11
from both sides of the equation
−
3
=
1
4
+
1
1
−
3
=
14
y
+
11
−3=14y+11
−
3
−
1
1
=
1
4
+
1
1
−
1
1
−
3
−
11
=
14
y
+
11
−
11
−3−11=14y+11−11
2
Simplify
Subtract the numbers
Subtract the numbers
again
−
1
4
=
1
4
−
14
=
14
y
−14=14y
3
Divide both sides of the equation by the same term
−
1
4
=
1
4
−
14
=
14
y
−14=14y
−
1
4
1
4
=
1
4
1
4
−
14
14
=
14
y
14
14−14=1414y
4
Simplify
Divide the numbers
Cancel terms that are in both the numerator and denominator